Surface Profiling Of Paper Radiated With Focused Infra-Red Nd:yag Pulsed Laser - Ali, Ahmad Hadi; Bidin, Noriah (Journal of Science and Technology, 2011)
A Nd:YAG pulsed laser with wavelength of 1.06 mm can cause a tremendous damage when interacts with material. In this study the effects of Nd:YAG laser interactions onto paper are reported. A combination lens technique was used with different focal length of lens. The target material that is a photographic paper was positioned at a focal spot of the laser beam. IR laser pulsed with peak power up to megawatt (MW) is brought to focus thus interacts with the photographic paper. This high-power impact of the laser pulsed shockwave caused a tremendeous damage on the photographic paper. Measurement of the impact was base on the surface size of the damage. From the observation result it shows that the maximum damage diameter for short lens system is 0.613 mm at peak power of 21.93 MW, whereas the maximum damage diameter for long lens system is 1.224 mm at 22.25 MW peak power.